2021
DOI: 10.1051/e3sconf/202130604004
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate contents in green juice prepared using either a high-speed blender or a masticating juicer

Abstract: Green vegetables are very beneficial for health, but sometimes it is not understood that some vegetables also contain anti-nutrients. For example, oxalic acid can be found in some green vegetables, such as spinach. Oxalic acid can be absorbed from food and as it is a toxin it has to be removed from the body via the kidneys. Under certain conditions, oxalate can combine with calcium in the kidneys forming stones which can lead to impaired kidney function. This study aims to compare two techniques for making veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The total amount of oxalate in blended and masticated spinach juice was much higher (3302.58-7638.27 mg/100g dw) than unpasteurised and pasteurised SPHJP [36]. Spinach is usually used as green juice because of its availability and lowpriced; hence, this study provides another alternative for green spinach, with a much lower level of oxalic acid.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The total amount of oxalate in blended and masticated spinach juice was much higher (3302.58-7638.27 mg/100g dw) than unpasteurised and pasteurised SPHJP [36]. Spinach is usually used as green juice because of its availability and lowpriced; hence, this study provides another alternative for green spinach, with a much lower level of oxalic acid.…”
Section: Resultsmentioning
confidence: 81%
“…In this study, haulm dregs (byproduct) were not included in the juice, lowering the oxalic acid levels. It had been proved that the discarded fibre spinach juice had reduced oxalates compared to the thick blended juice [36]. Meanwhile, more analysis on the total, soluble, and insoluble oxalates in sweet potato haulm must be determined in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Novitasari et al reported juice extraction using a high-speed blender and a masticatory juicer from a mixture of spinach (40% m/m), apple (15%), celery (11.25%), cucumber (11.25%), green pepper (7.5%), red pepper (7.5%), lemon (6%) and parsley (1.5%). 33 We therefore used a spiral oil press for extraction and total oxalic acid concentration was confirmed using 0.2 M hydrochloric acid to dissolve insoluble salts as described by Hönow et al 34 Some 0.33 mmol g −1 and 0.45 mmol g −1 of oxalic acid were extracted which was, respectively, 73 and 54% of the soluble fraction using high-speed blender and masticating juicer.…”
Section: Methodsmentioning
confidence: 99%